High resolution magnetostratigraphy and radio-isotope dating of early Pleistocene lake sediments from southern Armenia - Kirscher, Uwe; Bruch, A.; Gabrielyan, I.; Scharrer, S.; Kuiper, K.; Bachtadse, V. (2014)
The Pleistocene geology of Armenia is dominated by widespread occurrence of sediments recording recurring rapid and drastic changes of the environmental conditions during at least the last 2 million years. These sediments, predominantly diatomites, contain a huge variety of various fossil remains, allowing the reconstruction of flora, fauna as well as the climatic conditions especially during dispersal of early man into Eurasia 1.8 Ma. Radio isotope dating of pumice levels as well as a detailed magnetostratigraphic study have been carried out in Syunik Province near the town of Sisian, southern Armenia, in order to establish a temporal correlation of all major outcrops of paleo-lake sediments and to provide a timeframe for paleoenvironmental studies within this lake sediment succession.A total of 455 oriented drill cores was sampled at six large and four short sections with a sampling resolution between 5 and 20 cm. Detailed paleomagnetic experiments reveal the presence of a characteristic remanent magnetization (ChRM) pointing either to the north and down or south and up. A positive reversal test suggests the primary character of this magnetization component. Combining the normal and reverse polarity directions results in an overall sample mean direction of D = 354.8°, I = 51.5° with a Fisherian precision parameter k of 14.6 and the associated α95 of 2.9°, combining demagnetization data of 169 samples. In addition, ash layers were sampled for 40Ar/39Ar geochronology at five of the sections studied paleomagnetically and three additional small outcrops. The resulting ages range between 1.31 Ma and 1.08 Ma, with two samples yielding ~1.65 and 1.90 Ma. The latter are characterized by extremely low abundances of radiogenic 40Ar, suggesting that the mineral system has not been closed since the time of eruption, leading to substantial loss in Ar. Integration of these radio-isotope dates with the polarity data suggests that the normal polarities can be linked to the Jaramillo subchron within the Matuyama reversed polarity chron. Based on the longest interval of normal polarity identified at Ashotavan-2, a lower limit for the sedimentation rate of ~37 cm/ky can be estimated. Therefore, we infer the duration of lake sedimentation as ~350 ky, starting at ~1.4 Ma.